Pre-reading activity to improve students’ reading comrehension - Darwin, Darwin (Universitas Madako Tolitoli, 2024)
The objective of this research is to find out whether pre-reading activity can improve students reading comprehension of eight grade at SMP Negeri 3 Tolitoli or not. This is pre- experimental research design. The sample consisted of 26 students at class VIII D. The data were collected through Pretest and Posttest. The pretest was conducted to know the students prior knowledge before treatment, whereas posttest was accomplished to measure their knowledge after treatment. The researcher analyzed the data statistical. The result of the test showed that the students’ mean score in posttest 73.76 is higher that pretest 61.34. The testing hypothesis shows t-count 11,736 was higher than t-table 2.06. It indicates that null hypothesis is (HO) rejected and the alternative hypothesis (Ha) is accepted. In other words, the students’ reading comprehension can be improved through Pre-Reading Activity.